Pengembangan Perangkat Lunak Efisiensi Energi di Gedung Ins. Kabupaten X, Banten - Agung Wahyudi Biantoro (Universitas Mercu Buana, 2018)
ABSTRACT Electrical energy is one of the necessities of life that are important to us, but excessive consumption of electrical energy will bring adverse effects. The effort that needs to be done for energy efficiency is to conduct an energy audit in the building. An energy audit is one way to find out whether the level of energy consumption in the building, whether included in the wasteful or efficient category. In conducting the energy audit process it is necessary innovation for data processing can be done quickly and cost-effectively. Data processing is done by making software applications, using Visual Studio program that is connected with Microsoft Access as data storage. From the results of the research, the value of Energy Use Intensity (EUI or IKE) in Building Ins, Banten is 3.84 kWh / m2 / month or 46.02 kWh / m2 / year. It belongs to the very efficient category which is where to standardize office building that is 240 kWh / m2 / year. The average lighting condition of each room is still below the standard, which is below 240 lux, while the average AC temperature condition is 24.40C, in general has an efficient performance. The results of testing software applications are known to run well, with fast operation and can produce accurate data. Keywords: Energy Audit, EUI, Energy Efficiency, Software Energy Audit